Mechanism For Applying For Kredit Usaha Rakyat On Bank Rakyat Indonesia - Deni Mulyanto; Lisa Arisa (Review of Accounting and Taxation, 2022)
Purpose - The purpose of this writing is to find out how the procedure for granting People's Business Credit and for the process of approval or rejection of People's Business Credit. Design/methodology/approach - The method used in this research is descriptive qualitative research method. The techniques used in data collection where the data sources obtained are primary and secondary data. Finding - PT. Bank Rakyat Indonesia, Tbk has procedures that must be followed in granting People's Business Loans. In addition, PT. Bank Rakyat Indonesia, Tbk also applies the precautionary principle, this aims to minimize the risk of non-performing loans which can occur at any time. In the procedure for granting credit, there needs to be good cooperation between the bank and the debtor so that the credit granting process goes well. From the results of the discussion, the Procedure for Providing People's Business Credit (KUR) Case Study at PT. Bank Rakyat Indonesia, Tbk Karangantu Serang - Banten Branch Office is in accordance with predetermined procedures and the bank has criteria in overcoming processes that occur in the procedure for granting People's Business Credit so that the credit granting process can run properly and according to procedure.. Originality -